Comparison irisin peptide serum level in pregnant women with and without gestational diabetes mellitus: A case–control study - Zahra Mazloum Khorasani; Majid Besharat; Hassan Mehrad‐Majd; Seyed Ali Mohammadi; Malihe Mahmoudinia (Endocrinology, Diabetes & Metabolism, 2022)
Abstract Introduction Gestational diabetes mellitus (GDM) is a metabolic disease that affects mother and foetus during pregnancy, causing acute and chronic adverse effects. Irisin is proposed as a novel marker to predict GDM. The aim of this study was to assess the role of irisin peptide serum levels in gestational diabetes and compare with healthy pregnant women. Methods This case–control study was conducted on women at 24 to 34 weeks of gestation in Ghaem Hospital affiliated with Mashhad University of Medical Sciences between May 2016 and June 2019. In two study groups, GDM and non‐GDM women, an association between maternal serum irisin levels and clinical and biochemical parameters were evaluated. Maternal serum irisin levels were measured by an enzyme immunoassay method. Body mass index, serum levels of glucose, oral glucose tolerance test (OGTT), insulin, haemoglobin A1C, homeostatic model assessment of insulin resistance (HOMA IR) and irisin were evaluated. Results Totally, 56 participants (30 non‐GDM women and 26 women with GDM) were enrolled. Not statistically significant was observed in serum irisin levels between GDM and non‐GDM women. (p = .814) Irisin levels were not significantly associated with maternal age, systolic and diastolic blood pressure, the number of pregnancies, gestational age, fasting blood sugar, insulin, HOMA IR, one‐hour and two‐hour serum glucose and body mass index. Conclusions There is no significant difference between GDM and non‐GDM groups in the case of irisin value and later, no association of irisin with metabolic and anthropometric parameters. These findings need to be assessed in future experiments.